Effectiveness of Subcutaneous Tumor Necrosis Factor Inhibitors in Patients With Ankylosing Spondylitis: A Real-World Prospective Observational Cohort Study in China - Ji, Xiaojian; Wang, Yiwen; Hu, Zhengyuan; Ma, Yingpei; Man, Siliang; Li, Kunpeng; Wang, Yanyan; Zhu, Jian; Zhang, Jianglin; Huang, Feng (Frontiers in Pharmacology, 2019)
Objective: This prospective observational study investigated the efficacy of tumor necrosis factor inhibitors (TNFis) on disease activity, physical functionality, and mobility in patients with ankylosing spondylitis (AS) in a real-world setting. Methods: The Chinese Ankylosing Spondylitis Prospective Imaging Cohort (CASPIC) is an ongoing cohort study. Patients with AS were included to one of two groups: the TNFi user group included those who received TNFi at any time point; the non-TNFi user group included those who did not receive TNFi. Disease activity, physical functionality, and mobility were assessed by AS Disease Activity Scores (ASDAS), Bath AS Functional Index (BASFI), and Bath AS Metrology Index (BASMI), respectively. Results: A total of 804 patients with AS (241 TNFi users and 563 non-TNFi users) were recruited. For TNFi users, 83% received an etanercept biosimilar and 17.0% received adalimumab. Seventy-three TNFi users (30.3%) discontinued TNFis during the follow-up period; the mean duration of TNFi treatment was 6.9 ± 3.2 months. Reductions in ASDAS were significantly greater in TNFi users than in nonusers at 3, 6, and 12 months (differences in ASDAS reduction were 0.61, 0.56, and 0.46 units, respectively, all P < 0.05). Similarly, the improvement in BASFI was significantly greater in users than in nonusers at 3, 6, and 12 months (differences in BASFI improvement: 0.31, 0.75, and 0.74 units, respectively, all P < 0.05). BASMI increased in nonusers at 6 and 12 months (0.27, P = 0.47; 0.66, P < 0.001, respectively), but did not change in users (−0.16 and −0.13, respectively, both P > 0.05). At 12 months, changes in BASMI were significantly greater in nonusers than in users (−0.60, P = 0.47). Conclusion: TNFis are effective against disease activity and improve the physical functionality of patients with AS, even in those who taper or discontinue TNFis. Thus, TNFis may retard the progression of spinal mobility dysfunction in AS patients. TNF may maintain spinal mobility as indicated by the BASMI.